Active learning - Suzuki, Shintaro (Journal of The Showa University Society, 2024)
Active learning is a comprehensive term encompassing educational and instructional techniques that aim to elicit proactive learning from students; it does not refer to simple self-study or passive learning. Unlike the conventional cramming-style education that is prevalent in Japan, which has limitations in cultivating versatile skills and problem-solving abilities, active learning has been adopted globally, including in the United States. Students are expected to not only actively respond to a given task but also constantly contemplate and explore answers. Active learning is promoted by facilitating such activities among teachers and talented students. Japan’s Ministry of Education has redefined universities as institutions for higher education where students continuously learn throughout their lives and cultivate the ability to think independently. This definition anticipates graduates with high levels of bachelor’s competence, meaning individuals with outstanding international competitiveness. To this end, instructors need to create curricula that sustain students’ motivation for goal-setting and learning and stimulate intellectual curiosity. At medical schools, acquiring comprehensive abilities through active learning and a background in medical art are needed to cultivate professionalism in addition to the accumulation of knowledge. Finally, sincerity to patients is the most important attitude for medical professionals. That is what Showa University’s policy of “Shisei-Ikkann” means. For this purpose, the authors designed and constructed a new curriculum that provides opportunities for learning the abovementioned aspects while having fun. With respect to active learning, the most important point in promoting medical education is increasing learning engagement and the time for “out-of-class learning,” Leading educational institutions prioritize constructive discussions and creative group work as pillars of educational concepts with the concept of the physical classroom as a location in which vast amounts of knowledge are unilaterally accumulated gradually disappearing. By actively adopting the latest and most effective educational methods, such as flipped classrooms and gamification, and leveraging information and communications technology and the Internet of Things, the Showa University School of Medicine has implemented an advanced, sustainable curriculum compared with those of other medical schools. Various mechanisms have been developed to enhance students’ motivation; moreover, effective debriefing and peer teaching ensure a deep and long-term understanding of learned contents.